2018
DOI: 10.1016/j.pec.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

“Conversational Advice”: A mixed-methods analysis of medical residents’ experiences co-managing primary care patients with behavioral health providers

Abstract: Objective: When integrated behavioral health clinicians (IBHCs) and residents co-manage patients, residents may learn new approaches. We aimed to understand the effect of co-management on residents' behavioral health (BH) management learning. Methods: Residents completed a web-based survey enquiring: whether co-management included a shared visit and/or face-to-face meeting with an IBHC, whether residents received feedback from the IBHC, and what they learned. Qualitative responses were coded thematically using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…17 Therefore, future studies incorporating learners' perspectives on team-based, interdisciplinary training in IBH is important to inform IBH implementation. 17,[55][56][57] However, the detailed information gained here from clinical teams on the frontline of care can inform the development of IBH playbooks and curricula to support the design and implementation of effective IBH in clinical practice and training environments.…”
Section: Discussionmentioning
confidence: 99%
“…17 Therefore, future studies incorporating learners' perspectives on team-based, interdisciplinary training in IBH is important to inform IBH implementation. 17,[55][56][57] However, the detailed information gained here from clinical teams on the frontline of care can inform the development of IBH playbooks and curricula to support the design and implementation of effective IBH in clinical practice and training environments.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]16 Smith et al 17 concluded that effective residency curricula in biopsychosocial teaching include the following: a structured multidimensional approach that is a required activity and that balances learner-centered and teacher-centered approaches. The advent of increased BH integration in primary care clinics may offer residents a platform to learn BH skills 18,19 ; however, even within an integrated clinic such as the one studied, residents' experience with addressing mental health conditions is insufficient. Our residents' perspectives further strengthen the case for addressing residents' attitudes-which may deemphasize active management of mental health disorders-through increased mental health training within IM curricula.…”
Section: Discussionmentioning
confidence: 99%